Constraining Belief Pemilihan Pasangan pada Pria dan Wanita - Nurmala Febriani; Sri Fatmawati Mashoedi; Dian Wisnuwardhani (Jurnal Ilmiah Psikologi MIND SET, 2011)
This research was tried to see the Constraining Belief image of mate selection in male-female adolescents. It's including the seventh dimension mate selection constraining belief, that are One and Only, Love is Enough, Idealization, Complete Assurance, opposite Complement, and Cohabitation. The participants in this research are adolescents aged 23-34 years old, about 118 persons, 65 male and 53 female. Mate selection constraining belief is measured by using a tool, ARMSS (Altitudes about Romance and Mate selection Scale) which is developed by Cobb, Larson, and Watson (2003) based on the theory of mate selection constraining belief by Larson (1992). The result of this research showed that there were not any significant differences between man and woman.